Courseware to Learn About The Prophet Story: Saya Sayang Rasul (SSR) / Nur Mimi Adila Ismail - Ismail, Nur Mimi Adila (2015)
The Saya Sayang Rasul (SSR) courseware was introduce to give level 2 primary school students enjoyable experience and enhance student learning session for Pendidikan Islam subject. The multimedia elements such as graphic, animation, text, video and audio are manipulated to present the information in a more interactive way so that the student get better understanding and help them to memorize the important information especially about the history of our beloved prophet. The courseware can be one of the alternative tool for the teacher in teaching the Sirah topic with the information and the quizzes provided to examine the student understanding. SSR courseware is developed based on ADDIE model which consist of Analysis, Design, Development, Implementation and Evaluation phases. Additional phases which are the Preliminary Study and Documentation is added to complete this project. The evaluation phase has been conducted to 30 respondents and 2 Subject Matter Experts (SME) to examine usability of the courseware for the student and teacher. The questionnaires has 2 section, Section A is the Demographic profile and Section B is the User’s Acceptance. Based on the overall results shows, majority of respondents agreed that SSR courseware enhance their knowledge about prophet story with mean value is 4.73 (SD=0.52). As a conclusion, the findings shows that the respondents statisfied with the courseware. However, the courseware still needs future enhancement to make it more effective and comprehensive.